INDONESIA'S EMERGING THREAT: HOW NUCLEAR TRAFFICKING EXPLOITS NATIONAL VULNERABILITY - Fazha, Alvina Putri; Farisin, Mokhamad Saiful; Pinatih, Ni Komang Desy Setiawati Arya (Global and Policy Journal of International Relations, 2025)
Nuclear and radioactive trafficking has emerged as a critical issue on the global agenda, posing significant threats to national security and increasing the risk of terrorism. Developing nations such as Indonesia face unique challenges and vulnerabilities that render them particularly susceptible to such illegal activities. This study investigates the specific factors contributing to Indonesia's heightened risk of nuclear and radioactive trafficking, employing the Threat, Vulnerabilities, and Consequences (TVC) Framework as a structured analytical tool. Key issues examined include inadequate government awareness and response mechanisms, porous borders that facilitate the illicit movement of goods, and the presence of orphan sources, radioactive materials that are poorly tracked or uncontrolled. Furthermore, the analysis of potential risks and consequences highlights the serious implications of nuclear trafficking, including environmental damage, public health crises, and the potential for catastrophic terrorist attacks. The study reveals how exploitative actors may leverage Indonesia’s institutional and infrastructural weaknesses, emphasizing the urgent need for policy reform, capacity building, and strengthened regional cooperation. Ultimately, addressing these vulnerabilities is essential not only for Indonesia’s national security but also for regional stability and global safety. Keywords: Nuclear, Radioactive, Trafficking, TVC Framework, Indonesia